2014
DOI: 10.1186/1472-6882-14-164
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of pomegranate (Punica granatum) juice on testes against carbon tetrachloride intoxication in rats

Abstract: BackgroundPomegranate fruit has been extensively used as a natural medicine in many cultures. The present study was aimed at evaluating the protective effects of pomegranate (Punica granatum) juice against carbon tetrachloride (CCl4)-induced oxidative stress and testes injury in adult Wistar rats.MethodsTwenty eight Wistar albino male rats were divided equally into 4 groups for the assessment of protective potential of pomegranate juice. Rats of group I (control) received only vehicles and had free access to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
52
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 45 publications
8
52
0
1
Order By: Relevance
“…Study results revealed that pomegranate juice showed elevation in testosterone, luteinizing hormone and follicle stimulating hormone depleted after the injection of carbon tetra chloride (CCL4).Moreover, result also demonstrated that degeneration of germ and Leydig cells along with deformities in spermatogenesis due to the CCl 4 injections were restored with the treatment of pomegranate juice. 41 Another finding confirmed that extract and ascorbic acid administration reduced the deleterious effect of lead acetate on daily sperm production and epididymal sperm number. 42 Experiment was made to examine the effects of pomegranate juice consumption on sperm quality, spermatogenic cell density.…”
Section: Effect On Reproductive Systemsupporting
confidence: 66%
“…Study results revealed that pomegranate juice showed elevation in testosterone, luteinizing hormone and follicle stimulating hormone depleted after the injection of carbon tetra chloride (CCL4).Moreover, result also demonstrated that degeneration of germ and Leydig cells along with deformities in spermatogenesis due to the CCl 4 injections were restored with the treatment of pomegranate juice. 41 Another finding confirmed that extract and ascorbic acid administration reduced the deleterious effect of lead acetate on daily sperm production and epididymal sperm number. 42 Experiment was made to examine the effects of pomegranate juice consumption on sperm quality, spermatogenic cell density.…”
Section: Effect On Reproductive Systemsupporting
confidence: 66%
“…This explains the increased number of the proposed natural and synthetic anti-oxidative agents that treat reproductive hormonal imbalance and infertility induced by oxidative stress (35). Furthermore, recent results suggested that natural products containing anti-oxidants have the ability to protect testis against oxidative damages, lipid peroxidation, and impairment in anti-oxidant status induced by CCl 4 (3,13,35).…”
Section: Introductionmentioning
confidence: 98%
“…Spermatogenesis is orchestrated by two main regulations: endocrine [luteinizing hormone (LH) and follicle-stimulating hormone (FSH) from pituitary gland] and local intercellular communications mediated by a complex interplay of hormones and testicular growth factors, among which testosterone is crucial for testicular functioning (3). Recent studies concluded that oxidative stress, exhibited by exposure to toxic chemicals, causes a major damage to sperm quality by disrupting the anti-oxidant and reactive oxygen species (ROS) balance and thus resulting in abnormalities of spermatogenesis and male infertility (22,32).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is dire need to use some benign therapies such as ethnomedicines. Traditionally, ethnomedicines are being used extensively in the IndoPak region and elsewhere, mainly due to their costeffectiveness, easy accessibility, and perceived fewer side effects [10][11]. The mechanism of action of these herbal drugs is different in many respects from that of the synthetic drugs/pure compounds.…”
Section: Introductionmentioning
confidence: 99%